(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The leading intention of the project is to provide a new approach for image recognition using Python and its library in which we extensively use python libraries like numpy, Bing image downloader, matplotlib, sklearn and several others as well for the use of machine learning and its properties like support vector machine (SVM). An image recognition technique utilizing aa info of image characteristics is introduced. This method is totally different from chemist image method which needs an outsized quantity of knowledge of coaching set pictures in terms of the dimensions of every image and also the what reasonably pictures are they very. Especially, this system is helpful for recognizing pictures that have fastened form and structure like paintings and documents. Then we have a tendency to create use neural network that processes the individual pixels of a picture.